Umbral fitotoxico del bromacil para el cultivo del frijol (Phaseolus vulgaris L.) en suelo ferralitico rojo - Crespo Mesa, A.=700 1 Rodriguez Ortega, M.
(En, Es)
ilus., 16 ref.
Keywords: BROMACILO; FITOTOXICIDAD; FRIJOL(PHASEOLUS); SUELO; CUBA; SUELO ROJO